2017
DOI: 10.1088/1361-6439/aa631e
|View full text |Cite|
|
Sign up to set email alerts
|

A 3D-printed polymer micro-gripper with self-defined electrical tracks and thermal actuator

Abstract: This paper presents a simple fabrication process that allows for isolated metal tracks to be easily defined on the surface of 3D printed micro-scale polymer components. The process makes use of a standard low cost conformal sputter coating system to quickly deposit thin film metal layers on to the surface of 3D printed polymer micro parts. The key novelty lies in the inclusion of inbuilt masking features, on the surface of the polymer parts, to ensure that the conformal metal layer can be effectively broken to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In view of a mature integrated circuit, electric-driven 3D microactuators may be employed more widely due to their advantages [52,175]. For example, the sensor signal needs to be changed into an electrical signal to facilitate processing, while electrically driven microactuators enable the actuator and sensor components to be integrated [52,176]. The two large gaps that need to be bridged for practical electrical-driven 3D microactuators are materials and manufacturing strategies [177][178][179].…”
Section: Prospective Actuation Methods For 3d Microactuatorsmentioning
confidence: 99%
“…In view of a mature integrated circuit, electric-driven 3D microactuators may be employed more widely due to their advantages [52,175]. For example, the sensor signal needs to be changed into an electrical signal to facilitate processing, while electrically driven microactuators enable the actuator and sensor components to be integrated [52,176]. The two large gaps that need to be bridged for practical electrical-driven 3D microactuators are materials and manufacturing strategies [177][178][179].…”
Section: Prospective Actuation Methods For 3d Microactuatorsmentioning
confidence: 99%
“…The nominal diameter of the micro-gripper tip was 300 μm, while the effective force could reach values of between 0.01 and 0.04 N and the tip displacement varied between 20 and 80 μm, respectively. Alblalaihid et al [ 88 ] demonstrated the application of a sputter-coating process for the deposition of metallic layers on polymer components and validated their approach for the fabrication of a micro-gripper device ( Figure 1 C). They used a 3D projection micro-stereolithography (PMSL) system.…”
Section: Am Applications At the Microscalementioning
confidence: 99%
“…This technique can be divided into different categories based on the working principles. Fused deposition modeling (FDM) [102][103][104], micro continuous liquid interface production (μCLIP) [105], stereo lithography appearance (SLA) [106][107][108][109], and two-photon polymerization (2PP) [110] have been reported in the literature. 3D printing typically involves the use of polymers to fabricate CMMs.…”
Section: D Printingmentioning
confidence: 99%
“…SLA is a form of 3D printing technology, in which light causes the photopolymer to crosslink and form the body of a 3D solid. The photopolymers reported in the literature include well-established photo-curable materials such as trichlorofluoromethane (R11) [106], photo-curable polymer mixtures [107], and special photopolymer resins developed by 3D printing companies such as Formlabs [108]. The smallest feature resolution that can be reliably achieved by SLA ranges from 20 μm to 70 μm, as shown in Figure 11(a) and (b).…”
Section: D Printingmentioning
confidence: 99%